ANALSISI PERILAKU MASYARAKAT TERHADAP KEPUTUSAN MENGUNJUNGI DESTINASI WISATA SYARIAH DI SUMATERA BARAT - Ainun Mardiah; Herlinda Herlinda (Sosial Budaya, 2017)
This study aims to determine the influence of consumer behavior consisting of cultural, social, individual, and psychological factors which have simultaneous and partial influence on the decision to visit the Shariah tourism destination in West Sumatra. The number of sample is 100 respondents. The research variables consist of independent variables are culture (X1), social (X2), individual (X3), psychological (X4) as well as the dependent variable (Y) is the decision to visit the destination of sharia tourism. Data analysis used multiple linear regression analysis. The result of research indicate that culture has significant influence to the decision to visit shariah tourism destination, social has significant effect to the decision to visit the shariah tourism destination, the individual has a significant effect on the decision to visit the sharia tourism destination, the psychology has significant effect to the decision to visit the sharia tourist destination. Based on F test, it is found that cultural, social, individual and psychological variables influence together to the decision to visit the Shariah tourism destination in West Sumatera.